Seasonality and Cardio-Cerebrovascular Risk Factors for Benign Paroxysmal Positional Vertigo - Cao, Zhentang; Zhao, Xingquan; Ju, Yi; Chen, Meimei; Wang, Yan (Frontiers in Neurology, 2020)
Background: Benign paroxysmal positional vertigo (BPPV) is the most common cause of vertigo, especially in the elderly. Several studies have revealed a possible seasonality to BPPV. However, whether the seasonality of BPPV also exists in China is unclear. The characteristics of cardio-cerebrovascular risk factors for BPPV in the cold season have not yet been investigated. Objectives: 1) To investigate the seasonality of BPPV; 2) To explore the relationship between cardio-cerebrovascular risk factors and seasonality of BPPV. Methods: A retrospective observational study was performed in Beijing Tiantan Hospital from Jan 2016 to Dec 2018. The study included 1,409 new-onset BPPV patients aged 18-88 years. The demographic data, onset time, and medical history of BPPV were collected. The meteorological data, including temperature, atmospheric pressure, rainfall, and insolation, was obtained from Beijing Meteorological service. The x2 goodness of fit test was used to evaluate whether BPPV patients' numbers were significantly different among different months of the year. The Spearman correlation was used to detect the correlation between numbers of BPPV patients diagnosed monthly with each climatic parameter. The chi-square test for linear-by-linear association were used to investigate the relationship between cardio-cerebrovascular risk factor and seasonality of BPPV. Results: November to next March is the top 5 months with higher BPPV patient numbers (P＜0.001). The numbers of BPPV diagnosed monthly were conversely correlated with temperature and rainfall (r=-0.736, P=0.010; r=-0.650, P=0.022, respectively), positively correlated with atmospheric pressure (r=0.708, P=0.010), but no significant correlated with insolation. BPPV in the cold season (including January, February, March, November, and December) had a higher proportion, accounting for 54.2% of all BPPV patients. Among BPPV patients with ≥2, 1 and none cardio-cerevascular risk factors, the cold season accounted for 57.0%, 56.0%, 49.8%，respectively. As the number of cardio-cerebrovascular risk factors increased, the proportion of patients in the cold season of BPPV increased (P=0.025). Conclusions: BPPV patients are seen more in the months with low temperatures, low rainfall and high atmospheric pressure.Compared with the non-cold season, BPPV patients have more risk factors for cardio-cerebrovascular diseases in the cold season.